2019
DOI: 10.1038/s41598-019-48764-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of culture method on response to EGFR therapy in head and neck squamous cell carcinoma cells

Abstract: The EGFR pathway plays a critical role in head and neck squamous cell carcinoma (HNSCC). Targeted therapies against the EGFR are utilized as a treatment for HNSCCC. However, patient response is heterogeneous and molecular biomarkers are lacking to predict patient response. Therefore, functional assays where drug response is directly evaluated in tumor cells are an interesting alternative. Previous studies have shown that experimental conditions modify the drug response observed in functional assays. Thus, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…It has been demonstrated that PDOs from HNC can recapitulate the morphologic and molecular characteristics of the original tumor [33,34]. In addition, PDOs can be readily used to test sensitivity to multiple drugs and radiation due to their relatively rapid 3D culture (i.e., days), compared to the lengthy process of establishing PDXs (i.e., weeks to months) [35]. We have recently demonstrated an approach to testing radiation sensitizers using PDOs derived from a panel of colon cancer patients [36] and have active projects utilizing this approach in HNC.…”
Section: Organoid Modelsmentioning
confidence: 99%
“…It has been demonstrated that PDOs from HNC can recapitulate the morphologic and molecular characteristics of the original tumor [33,34]. In addition, PDOs can be readily used to test sensitivity to multiple drugs and radiation due to their relatively rapid 3D culture (i.e., days), compared to the lengthy process of establishing PDXs (i.e., weeks to months) [35]. We have recently demonstrated an approach to testing radiation sensitizers using PDOs derived from a panel of colon cancer patients [36] and have active projects utilizing this approach in HNC.…”
Section: Organoid Modelsmentioning
confidence: 99%
“…days), compared to the lengthy process of establishing PDXs (i.e. weeks to months) [30]. We have recently demonstrated an approach to testing radiation sensitizers using PDOs derived from a panel of colon cancer patients [31] and have active projects utilizing this approach in HNC.…”
Section: Organoid Modelsmentioning
confidence: 99%
“…Humanized mouse models offer a potential solution to this problem as they are immunocompromised to allow for PDX growth, but are then engrafted with a partially functional "human" immune system allowing for the study of the immune response [36]. Humanized animal models offer the opportunity for investigators to study immunomodulatory agents in human cancers (28,(30)(31)(32), work that has taken on greater importance since the 2019 approval of pembrolizumab in the first-line setting for metastatic HNC patients.…”
Section: Humanized Modelsmentioning
confidence: 99%
“…Moreover, in this work we demonstrated that 2D experiments cannot be extrapolated to 3D cultures as 3D cultures are less sensitive to cell death induction. In conclusion, 3DELTA is a more cost-effective way to identify and measure cell death type in 3D cultures, including spheroids.Cells 2020, 9, 703 2 of 13 3D structures, such as spheroids, better represent in vivo drug resistance, as they form a more dense barrier for the drugs to cross, compared to 2D systems [12], with the core of the structure being most protected against the drugs. Therefore, with regard to the responses to therapy, including to cell death, 3D structures are better test models for drug screening compared to 2D monolayers [13].Spheroids are one of the most widely used 3D models and can be formed by seeding cells in nonadherent plates allowing for self-assembly ( Figure 1A) [7].…”
mentioning
confidence: 99%
“…Cells 2020, 9, 703 2 of 13 3D structures, such as spheroids, better represent in vivo drug resistance, as they form a more dense barrier for the drugs to cross, compared to 2D systems [12], with the core of the structure being most protected against the drugs. Therefore, with regard to the responses to therapy, including to cell death, 3D structures are better test models for drug screening compared to 2D monolayers [13].…”
mentioning
confidence: 99%